2018
DOI: 10.1590/1983-40632018v4852495
|View full text |Cite
|
Sign up to set email alerts
|

Physiological behavior of melon cultivars submitted to soil salinity1

Abstract: Melon is one of the most important vegetables for the Brazilian foreign trade. However, in semi-arid areas, the irregular rainfall, excessive use of fertilizers and, especially, poor quality water contribute to the soil salinization, becoming a limiting factor and damaging the photosynthetic apparatus, as well as affecting yield. This study aimed to evaluate the physiological behavior of melon cultivars submitted to soil salinity. For that, an experiment was conducted in a greenhouse, using a randomized block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Decreases of 62.66%, 17.13%, 14.20%, and 23.65% were found for stomatal conductance (Figure 3A), CO 2 assimilation rate (Figure 3B), internal CO 2 concentration (Figure 3C), and transpiration rate (Figure 3D), respectively, when comparing the treatments with the lowest and highest salinity levels. The inhibition in stomatal conductance may be related to excess salts in the soil solution, causing a reduction in water absorption, promoting stomatal closure, and inhibiting leaf gas exchange (PARIHAR et al, 2015;SOUSA et al, 2018;SILVA et al, 2019). Similar results were found in other studies (RIBEIRO et al, 2020;FREITAS et al, 2021;FREIRE et al, 2021).…”
Section: Resultssupporting
confidence: 82%
“…Decreases of 62.66%, 17.13%, 14.20%, and 23.65% were found for stomatal conductance (Figure 3A), CO 2 assimilation rate (Figure 3B), internal CO 2 concentration (Figure 3C), and transpiration rate (Figure 3D), respectively, when comparing the treatments with the lowest and highest salinity levels. The inhibition in stomatal conductance may be related to excess salts in the soil solution, causing a reduction in water absorption, promoting stomatal closure, and inhibiting leaf gas exchange (PARIHAR et al, 2015;SOUSA et al, 2018;SILVA et al, 2019). Similar results were found in other studies (RIBEIRO et al, 2020;FREITAS et al, 2021;FREIRE et al, 2021).…”
Section: Resultssupporting
confidence: 82%
“…In contrast, iCE and WUE were not significantly influenced by either factor studied, possibly because they are mathematical relationships, such as the ratio between the carbon dioxide assimilation rate and intracellular CO 2 concentration (iCE), as well as the ratio between the CO 2 assimilation rate and conductance (WUE), as observed by Sousa et al (2018).…”
Section: Resultsmentioning
confidence: 93%
“…When analyzing the interaction between the electrical conductivity of irrigation water and H 2 O 2 concentrations, it was observed that the LA (Figure 2A), DMAP (Figure 2B), and P of melon plants (Figure 2C) subjected to ECw of 0.3 dS m -1 differed significantly from that of plants irrigated with water at 5.0 dS m -1 . This was due to high saline concentrations reducing melon growth and production (Sousa et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation